The Schøyen Collection : manuscripts from around the world spanning 500 years of human culture & civilisation - Schøyen Collection (2000)
[Dt.:] Die Schøyen Collection ist eine Privatsammlung mit Schwerpunkt auf Manuskripten (aus allen Epochen, Zeiten und Regionen). Sie befindet sich in Oslo und London. Über die Datenbank ist es möglich, die Abbildungen zu vergrößern und Details durch eine Zoom-Funktion zu betrachten. - [Engl.:] The Schøyen Collection comprises most types of manuscripts from the whole world spanning over 5000 years and is located mainly in Oslo and London. The present website comprises a selection of digital descriptions of manuscripts with sample images from The Schøyen Collection.